Sola fides at the Core of Varieties: Luther as Religious Genius in William James's Thought? - Viale, Claudio Marcelo (2015)
The purpose of this article is to show the great influence of Luther's conception of religion on James' Varieties of Religious Experience. I will argue that James's conception of religion should be interpreted as a philosophical course of Lutheranism; and that, as a course of Lutheranism, James's conception of religion infers the most radical consequences of the Lutheran principle of sola fides.